2015
DOI: 10.1016/j.ces.2014.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Critical agitation for microcarrier suspension in orbital shaken bioreactors: Experimental study and dimensional analysis

Abstract: Experimental characterization of particle suspension in orbital shakers. New correlation predicting critical agitation conditions for complete particle suspension. Larger orbital diameters promote smaller power dissipations at complete particle suspension. a b s t r a c tOrbital shaken bioreactors are widely used at the laboratory scale for the culture of animal cells in suspension mode. In the case of adherent-dependent cell lines, the choice of agitation conditions at which all particles are just-suspended (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“… for larger reactors ( d i = 10–125 cm) indicated that the Froude number ratio, Fr / Fr cr , is an effective scaling parameter for mixing time measurements in shaken cylinders under a wide range of operating conditions. The flow transition identified by the Froude number ratio was also found to accurately predict the full suspension speed of microcarriers across different bioreactor geometries (cylindrical vessels and flasks) and scales , . The two‐phase PIV study of Pieralisi et al.…”
Section: Introductionmentioning
confidence: 86%
“… for larger reactors ( d i = 10–125 cm) indicated that the Froude number ratio, Fr / Fr cr , is an effective scaling parameter for mixing time measurements in shaken cylinders under a wide range of operating conditions. The flow transition identified by the Froude number ratio was also found to accurately predict the full suspension speed of microcarriers across different bioreactor geometries (cylindrical vessels and flasks) and scales , . The two‐phase PIV study of Pieralisi et al.…”
Section: Introductionmentioning
confidence: 86%
“…They were selected based on the EB sedimentation characteristics and sizes (iBET group, unpublished data). Microcarriers were stained using 0.4 % Trypan Blue (Sigma-Aldrich, USA) to aid in visualization (Olmos et al, 2015), and experiments were conducted at a concentration of 1 g/L. Concentrations closer to those employed in cell culture experiments (0.0375 g/L at the start of differentiation and 0.2 g/L at the end) could not be detected by the camera.…”
Section: Suspension Characterization Experimentsmentioning
confidence: 99%
“…Suspension should therefore be characterized to quantify the minimum speed required for off-bottom suspension and homogeneity, but also to characterize the degree of settling during intermittent agitation modes. Off-bottom suspension has been studied in-depth (Ibrahim and Nienow, 2004;Nienow et al, 2016), however objective techniques and reproducible protocols should be used to quantify suspension (Olmos et al, 2015;Pieralisi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…while the suspended to critical Froude number ratio tends to drift further away from the dashed reference line at F r s /F r cr = 1.1 as h/d i/ √ do/d i increases above 1. It is interesting to note that the suspension speed data obtained by Olmos et al (2015) in Erlenmeyer flasks showed a good scaling with the critical speed, N cr , also for…”
Section: Microcarriers Suspension Speedmentioning
confidence: 72%